Aula: o intervalo existente entre o que os professores dizem e o que realizam como prática social - Beck, Eliane Maria Cabral (2017)
This research takes as an object of reflection and analysis the classroom environment and more specifically, the 'class', the moment the teacher puts the teaching work in practice. Based on studies and empirical knowledge about the subject, some questions stand out as guiding elements of the present investigation: how the teacher imagines his classroom and where that imaginary comes from, what he teaches beyond systematized knowledge and if he passes value judgments in this activity. In order to deal with this problematization, it is sought to investigate some conceptions that guide the teacher formation process towards the concepts about "class", "student" and "content". The general objective is to see if there is any gap between what theachers say that a lesson would be and what, in recorded lessons, these teachers have performed as practice. In the perspective of reaching the proposed objective, the research is based on the conception that every sequence of statements offers possibilities of interpretation. Having as theoretical reference the Discourse Analysis of the French Line, the analyzes are based on these theoretical assumptions, such as the notions of Subject and Social, Ideological and Discursive Formation, among others, that are brought to the discussion. The corpus of the research consists of discursive sequences resulting from interviews and class recordings of six teachers from an educational institution. In general, the teacher and the student are considered as representatives of determined places in the structure of a social formation, which allows constructing interpretations without the pretension of generalizations.